Detection of Polyomavirus BK and JC in kidney Transplant Recipients - mohammed, taqwa; dawood, dawood (Iraqi National Journal of Nursing Specialties, 2016)
objectives: To investigate the polyomaviruses (BK, JC) in asymptomatic kidney transplant recipients and healthy persons as control. It is one of the first reports on serological detection and molecular characterization that describes the circulation of polyomaviruses (BKV, JCV) have been done in Iraq recently. Methodology: The present study was designed as prospective case control study was done during the period from November 2015 to August 2016. Total of 97 serum and urine samples were collected randomly from 25 healthy control person and 72 renal transplant recipients, attending Iraqi Renal Transplantation Society. “New experimental indirect ELISA kit" had been designed and synthesized manually for detection Anti-JCV IgM and IgG, Urea and creatinine level had been measured for total study groups for estimation of renal functions. Results: All of the samples were submitted to a Nested-PCR. A significantly difference had been seen (P < 0.01) of PyV was found in renal transplant patients 2(2.8%) in comparison to the control group 4(16.0%). JCV was detected in.6 (6.2%) samples (2 patients/ 4 controls).by conventional PCR, BKV was detected in 2(2.8%) of renal transplant group and not detected with any one of control group. result for IgM revealed positivity for 25(25.8%) out of 72cases of renal transplant subject and 8(8.2%) person out of 25control groups. for IgG the result show that 21(29.2%) out of 72 cases of renal transplant Subjects have a positive result for IgG but this antibody was not detected in the control. Recommendations: Success diagnosis required sensitive assay typically Nested-PCR to detect extremely low viral load present in potential kidney donor before access as a donor, Because of the potentially harmful effects of polyomavirus which may cause loss of the transplanted kidney